Underground Measurements of Nuclear Reaction Cross-Sections Relevant to AGB Stars - Chemseddine Ananna; Francesco Barile; Axel Boeltzig; Carlo Giulio Bruno; Francesca Cavanna; Giovanni Francesco Ciani; Alessandro Compagnucci; Laszlo Csedreki; Rosanna Depalo; Federico Ferraro; Eliana Masha; Denise Piatti; et al. (Universe, 2021)
Nuclear reaction cross sections are essential ingredients to predict the evolution of AGB stars and understand their impact on the chemical evolution of our Galaxy. Unfortunately, the cross sections of the reactions involved are often very small and challenging to measure in laboratories on Earth. In this context, major steps forward were made with the advent of underground nuclear astrophysics, pioneered by the Laboratory for Underground Nuclear Astrophysics (LUNA). The present paper reviews the contribution of LUNA to our understanding of the evolution of AGB stars and related nucleosynthesis.